Calculation method and evaluation of surrounding rock pressure of vertical shaft - Zhongxi Tian; Yuanwu Sun; Qingshuang Zhao; Boliang Zhang; Wanrong Liu; Xutao Zhang (Scientific Reports, 2024)
Abstract The surrounding rock pressure of vertical shafts is one of the basic parameters of shaft lining design. Investigating its calculation methods and applicable scopes has great engineering significance. The paper classifies and compares the calculation methods, discusses the application scopes of various calculation methods, and proposes that the axisymmetric layered method is highly consistent with the field monitoring data for the calculation of surrounding rock pressure of vertical shafts in bedrock sections on the basis of practical engineering examples. On the basis of Terzaghi theory, the calculation formula of surrounding rock pressure of vertical shaft in inclined rock strata with single group joints is derived. The formula can reflect the influence of rock strata dip angle and joints.